Children and the youth in rural Viet Nam - Gaia Narciso; Carol Newman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Structural transformation in rural Viet Nam has led to rising incomes and a diversification of livelihoods away from agriculture. Using panel data on children in 2,181 rural households surveyed over the 2008-14 period, we examine how the welfare of children has been impacted by structural transformation. Our analysis depicts a society that has made great progress towards improving child welfare which can in part be linked to the empowerment of women that has accompanied the transformation process. We find heterogeneity in welfare gains though, with boys benefitting more than girls and persistently lower levels of child welfare among ethnic minorities.
Keywords: O12; D1; J13; 330; child welfare; child labour; education; gender; structural transformation; Viet Nam